2022
DOI: 10.3390/nu14173462
|View full text |Cite
|
Sign up to set email alerts
|

Intrahepatic Fat Content and COVID-19 Lockdown in Adults with NAFLD and Metabolic Syndrome

Abstract: Background: COVID-19 lockdowns had a significant impact on people’s health, triggering levels of anxiety, perceived stress, and changes in food and nutritional status. Objectives: To assess the changes in dietary habits, metabolic syndrome (MetS) and liver parameters before and after the COVID-19 lockdown according to changes in intrahepatic fat content in adults with non-alcoholic fatty liver disease (NAFLD) and MetS. Design: Pre- and post-lockdown observation of the COVID-19 lockdown on fifty-nine 40–60-year… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 71 publications
0
2
0
Order By: Relevance
“…A retrospective cross-sectional study from the Yale Study of the Pathophysiology of Prediabetes/Type 2 Diabetes in youth showed an increased prevalence of NAFLD in adolescents with obesity (from 37.3% in 2017–2019 to 60.9% in 2020–2022) with a worsening of their metabolic status [ 15 ]. Accordingly, several studies showed an increase in body weight, glycemia, transaminases, and intrahepatic fat content in subjects during pandemic, with a growing risk of progression to NASH and fibrosis [ 16 , 17 ].…”
Section: Epidemiologymentioning
confidence: 99%
“…A retrospective cross-sectional study from the Yale Study of the Pathophysiology of Prediabetes/Type 2 Diabetes in youth showed an increased prevalence of NAFLD in adolescents with obesity (from 37.3% in 2017–2019 to 60.9% in 2020–2022) with a worsening of their metabolic status [ 15 ]. Accordingly, several studies showed an increase in body weight, glycemia, transaminases, and intrahepatic fat content in subjects during pandemic, with a growing risk of progression to NASH and fibrosis [ 16 , 17 ].…”
Section: Epidemiologymentioning
confidence: 99%
“…Right after that, the 3-month period of the Coronavirus disease 2019 (COVID-19) national lockdown started, and both groups started to gain weight [180]. In fact, the COVID-19 lockdown posed a threat to healthy lifestyles, as proven by several studies reporting weight gains and the worsening of the disease control in the overall NAFLD population [181][182][183]. However, patients in the intervention group experienced less weight gain (3.1 ± 1.6 kg vs. 0.7 ± 1.7 kg, p < 0.001) and lower alterations in their dietary habit patterns compared to the controls, also being more likely to maintain their physical activity levels [180].…”
Section: Lifestyle Treatment Of Nafld In People With Hivmentioning
confidence: 99%